THE ROLE OF NOTICING AND WORKING MEMORY CAPACITY IN L2 ORAL PERFORMANCE - Bergsleithner, Joara Martin (Organon, 2011)
! is study investigates how noticing of L2 instances in input re-lates to working memory (WM) capacity and to grammatical accuracy inL2 oral tasks. Participants were 30 Brazilian adult learners of English whowere required to perform " ve tasks aimed at assessing (a) WM capacity,(b) grammatical accuracy in oral performance, and (c) noticing of formalaspects of a target structure. ! e results show that there are statisticallysigni" cant relationships among noticing of L2 formal features, grammati-cal accuracy in L2 oral performance and WM capacity. Together, the re-sults can be taken as evidence that learners with a larger WM capacityare also more prone to noticing L2 formal aspects and to performing moregrammatically accurate speech in the L2.